Occurrence of Nine Grapevine Viruses in Commercial Vineyards of Mendoza, Argentina - Gómez Talquenca, Sebastián (2023)
Grapevine is a widely grown fruit crop that is seriously affected by different viruses, reducing grape yield and quality, as well as threatening profitability. Vineyard disease management requires accurate identification of viral infections. This study aimed to survey the presence of ten grapevine viruses in four geographic sites in the Mendoza province of Argentina. Two hundred twenty-three composite cane samples from 1060 plants of six cultivars were collected from 26 blocks distributed across 11 vineyards. The cane samples were screened by RT-PCR for the following viruses: grapevine leafroll-associated viruses 1–4 (GLRaV 1, 2, 3, and 4), grapevine fanleaf virus (GFLV), grapevine fleck virus (GFkV), grapevine virus A (GVA) and B (GVB), grapevine rupestris stem pitting associated virus (GRSPaV), and arabis mosaic virus (ArMV). The results showed an uneven occurrence of viruses through the sampled regions, with GRSPaV being prevalent (71.1%), followed by GFLV (28.9%), GFkV (20.6%), and GLRaV-2 (14.7%). GVB was not detected. This study revealed a moderate prevalence of viruses associated with economically impactful diseases in the vineyards surveyed.